Service Transformation Training as an Effort to Strengthen the Quality of Service of Village Credit Institutions - Setiawati, I Gusti Ayu Ety; Praptayani, Luh Anggie Deasy; Yuesti, Anik; Rustiarini, Ni Wayan; Menes, Carmen C.; Madrigal, Dennis Villasor; Alve, Joel Arante; Ituriaga, Christian Angelo B. (Jurnal Abdimas Mandiri, 2026)
Transforming Village Credit Institution (LPD) services has become an urgent need amidst the competition and dynamics of the global financial system. However, the demand for improved service quality is not matched by human resource knowledge, necessitating service transformation training at microfinance institutions. Furthermore, a limited understanding of service experience and the suboptimal use of digital service channels can undermine customer satisfaction and trust. This community service activity aims to improve the LPD's human resource knowledge in the Kukuh traditional village through training in transforming traditional services into professional patterns. The community service partners are all LPD employees in the Kukuh traditional village who are directly involved in the customer service process. The community service implementation method is designed using a participatory and applied approach. The results of the activity evaluation showed that post-test scores increased for almost all participants compared to the pre-test. This figure indicates an increase in knowledge of the concept of professional service and LPD service transformation. This activity has implications for changing employee perspectives on the meaning of service. Service is no longer perceived as a mere administrative activity but rather as a strategic process for building trust, loyalty, and the LPD's institutional image. Thus, this community service activity not only provides short-term benefits, such as increased knowledge, but also has the potential to encourage sustainable changes in service behavior.